Energy and climate policy: Quantifying the benefits of a European approach - Mathias Mier (CESifo GmbH, 2024)
The European Emissions Trading System is a cornerstone of the EU climate policy and its development is set until 2030. However, it is unclear what will happen afterwards. This policy brief compares three different scenarios: Rapid Decarbonization, 2050 Climate Neutral and a Break scenario. The simulations quantify the total benefits of a joint European effort at EUR 248 billion between 2024 and 2050. In the worst-case scenario, total costs could reach EUR 8.629 trillion.
Keywords: 330